The Acts of Salonitan metropolitan councils held in 530 and 533 - an analysis (Archaeologia Adriatica, 2009)
This article analyzes the Acts of the Salonitan Metropolitan Councils (concilia metropolitana Salonitana) held on the 15th of July 530 and the 4th of May 533 under the aegis of the archbishop of Salona (archiepiscopus Salonitanus) Honorius the Younger (528-547). The participants signed them according to the importance of their dioceses, or status, starting from the archbishop himself to the factorum (primas) of the very last Dalmatian bishopric (to 530), or rather the bishops of three newly established dioceses (533). The Acts from 530 were further signed by the Salonitan archpresbyter, four presbyters of undefined diocesan identity, and probably two representatives of the monastic communities (patres). The Acts from 533 were signed only by bishops, which is understandable given the fact that during this Council the question was solved of the reorganization of the church in Dalmatia and the Salonitan metropolitan district and the consecration of new bishops. The Acts of both Councils were also signed by the bishop of Siscia in Pannonia, not merely because his diocese, just like Dalmatia, from 493 onwards had been under the authority of the Ostrogoths, but probably also because this bishopric was faced with problems similar to those of the church in Dalmatia.
Keywords: Church in Dalmatia; Salonitan Metropolitan Councils (concilia metropolitana Salonitana); Salonitan archbishop Honorius the Second (528-547)